Coriander essential oil attenuates dexamethasone-induced acute liver injury through potentiating Nrf2/HO-1 and ameliorating apoptotic signaling. (April 2023) - Mahmoud, Mona F.; Ali, Noura; Mahdi, Ismail; Mouhtady, Omar; Mostafa, Islam; El-Shazly, Assem M.; Abdelfattah, Mohamed A.O.; Hasan, Rehab A.; Sobeh, Mansour
Graphical abstract: Highlights: Coriander essential oil (CO) attenuates dexamethasone-induced liver toxicity. CO improved liver markers and reduced oxidative stress. CO prevents tissue damage and fibrosis and decreases hepatic apoptosis. CO enhances Nrf2/HO-1 and antiapoptotic signaling pathways. Abstract: Coriander essential oil extracted from the fruits of Coriandrum sativum is rich in linalool, γ-terpinene and α-pinene. Herein we examined the possible hepatoprotective effects of coriander essential oil on dexamethasone-induced liver injury and the possible mechanisms. Coriander essential oil at the doses of 0.5 and 1 mL/kg or metformin (50 mg/kg) was orally administered to rats for four days, one hour before dexamethasone subcutaneous injection. Liver injury was enhanced in dexamethasone-injected rats as manifested by monocyte infiltration, hepatocyte degeneration and collagen deposition besides elevated ALT and AST levels. This was accompanied by decreased Nrf2/HO-1 signaling, leading to increased lipid peroxidation and reduced glutathione depletion. Liver-antiapoptotic protein, Bcl2 was reduced, and caspase 3 expression was increased showing hepatocyte apoptosis following dexamethasone injection. Coriander essential oil dose-dependently reversed the previous changes. These findings suggest that coriander essential oil could ameliorate dexamethasone-induced liver injury via Nrf2/HO-1 and antiapoptotic signaling pathways.